(untitled) (Medico Legal Update, 2020)
The objectives were to assess the level of anxiety among diabetes mellitus patients and to associate the level of anxiety with demographic variables among diabetes mellitus patients. The convenience sampling was used to select 73 diabetes mellitus patients. The data collected tools were validated and reliability was established. The data were collected by Hamilton anxiety rating scale. The collected data was Tabulated and Analyzed. Descriptive and Inferential statistical method were used. The study showed that maximum diabetes patients were above 60 years (34%); Majority of the patients were females (58%); Majority of the diabetes patients were moderate workers (37%); Majority of the patients were married (86%); Majority of the diabetes patients were duration of diabetes 1-3 years (48%); Majority of the diabetes patients not worried about health condition; But (48%) of the patients says that they worried about complication (43%). The study showed that 48% of diabetes patients have mild anxiety, 36% of diabetes patients have mild to moderate anxiety 16% of diabetes patients have moderate to severe anxiety. It showed that there is no significant association between level of anxiety among diabetes patients with selected demographic variables like age (?2=5.635), gender (?2=2.105), occupation (?2=3.969), marital status (?2=5.671), duration of diabetes (?2=0.263). There is significant association between level of anxiety among diabetes mellitus patients with selected demographic variables like Are you worried about the health condition (?2=8.68).